Rural Economy Knowledge Support System (REKSS) - Nigeria Institutional and Individual Dataset - International Food Policy Research Institute (International Food Policy Research Institute, 2010)
This survey was conducted to identify the current capacity within Nigeria for providing evidence for policymaking and for creating this capacity for future generations. This is part of the program to support the designing and implementing of evidence-based, pro-poor, gender sensitive and environmentally sustainable agricultural and rural development policies and strategies in Nigeria. The data presented originates from the survey conducted in 2008. A total of 25 institutions and 184 individuals were sampled. Topics covered for institutions include statements seeking to establish an understanding of the agricultural and rural policy environment and process, institution and institutional environment, financial resource management, human resources management, staff performance and performance appraisal, organizational management, autonomy in personnel and budgetary issues, and technical capacity. Topics covered for individuals include background information about respondent, experience with the agricultural and rural development policy process, gender in the policy process, environmental issues in the agricultural and rural development policy process, job satisfaction and institutional incentives.